2015
DOI: 10.1073/pnas.1418491112
|View full text |Cite
|
Sign up to set email alerts
|

Endocytic proteins drive vesicle growth via instability in high membrane tension environment

Abstract: Clathrin-mediated endocytosis (CME) is a key pathway for transporting cargo into cells via membrane vesicles; it plays an integral role in nutrient import, signal transduction, neurotransmission, and cellular entry of pathogens and drug-carrying nanoparticles. Because CME entails substantial local remodeling of the plasma membrane, the presence of membrane tension offers resistance to bending and hence, vesicle formation. Experiments show that in such high-tension conditions, actin dynamics is required to carr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
155
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(167 citation statements)
references
References 60 publications
11
155
1
Order By: Relevance
“…The requirement for two distinct mechanisms in two regions of neck radii could be related to the energy barrier that we found as the neck radius of the catenoid decreases. Other evidence of switch-like behaviors are found in endocytosis where multiple studies have reported the existence of a snap-through instability 35,[64][65][66] . Furthermore, soap films, with no bending rigidity, also exhibit a structural instability when held as catenoids 45,67 .…”
Section: Discussionmentioning
confidence: 95%
“…The requirement for two distinct mechanisms in two regions of neck radii could be related to the energy barrier that we found as the neck radius of the catenoid decreases. Other evidence of switch-like behaviors are found in endocytosis where multiple studies have reported the existence of a snap-through instability 35,[64][65][66] . Furthermore, soap films, with no bending rigidity, also exhibit a structural instability when held as catenoids 45,67 .…”
Section: Discussionmentioning
confidence: 95%
“…We use a modified version of the Helfrich energy that includes spatially varying spontaneous curvature C (θ α ) bending modulus κ(θ α ) and Gaussian modulus κG (θ α ) (42,48,50,52),…”
Section: Membrane Tensionmentioning
confidence: 99%
“…where ∆ is the surface Laplacian, p is the pressure difference across the membrane, λ is interpreted to be the membrane ten- sion, b αβ are components of the curvature tensor, f is a force per unit area applied to the membrane surface, and n is the unit normal to the surface (42,50). In this model, f represents the applied force exerted by the actin cytoskeleton; this force need not necessarily be normal to the membrane.…”
Section: Membrane Tensionmentioning
confidence: 99%
“…The shape transitions occur as a result of lateral loading on the membranes from cytoskeletal filaments, such as actin, from osmotic pressure gradients across the membrane, or from reference configuration of finite element e membrane-protein interactions. For example, in endocytosis -a primary mode of transport of cargo between the exterior of the cell and its interior -proteins bind to the flat membrane and induce invaginations or bud shapes, followed by a tube formation by actin-mediated pulling forces [35,64].…”
Section: Introductionmentioning
confidence: 99%